Multiple diagnostic modalities are appropriate for detecting Nannizziopsis guarroi in experimentally infected bearded dragons (Pogona vitticeps) - Wong, Amanda D.; Adamovicz, Laura; Dalen, Jacob P.; Bender, Alexander M.; Rosser, Michael F.; Imai, Denise M.; Terio, Karen A.; Reinhart, Jennifer M.; Allender, Matthew C.; Keller, Krista A. (Frontiers in Amphibian and Reptile Science, 2025)
IntroductionNannizziopsis guarroi causes mycotic dermatitis, colloquially known as “yellow fungus disease”, in lizards. Several fungal diagnostic assays may detect this microbe in clinical cases, but the clinical performance of these assays has yet to be explored.MethodsSix adult bearded dragons were topically exposed to N. guarroi along the dorsal midline and serially sampled over five months as clinical cutaneous lesions developed.ResultsThe median dates of first test positivity for fungal culture, quantitative polymerase chain reaction (qPCR), and commercially available next-generation sequencing (NGS) were 28, 6, and 17.5 days prior to lesion development, respectively. Lesions did not fluoresce under long-wave ultraviolet illumination. Femoral pores were a site of infection in all four male lizards, representing a novel presentation. Additionally, one lizard developed subclinical granulomatous N. guarroi pneumonia. Postmortem assessment of diagnostics identified a high level of agreement between histopathology, fungal culture, and qPCR; however, cytologic agreement with histopathology was poor.DiscussionFungal culture, qPCR, and NGS are appropriate screening tools for the detection of N. guarroi prior to the onset of cutaneous lesions and may be used as diagnostic tools to confirm N. guarroi infection in clinically affected bearded dragons.